Structure, sequence and ion-exchange of left-handed G-quadruplexes - Bakalar, Blaz (2019)
Besides the canonical double-stranded helical B-DNA structure, DNA can form four-stranded G-quadruplex structures composed of stacked guanine G-tetrads.